1998
DOI: 10.1007/978-1-4615-5331-1_53
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of JHMV-Specific CTL in the Cns in the Absence of CD4+ T Cells

Abstract: The role of CD4+ T cells in altering the activity of cytotoxic T lymphocytes (CTL) during infection of the central nervous system (CNS) by the neuroptropic JHMV strain of mouse hepatitis virus was examined. Adoptive transfer of in vitro activated CTL into CD4-depleted and control recipients showed that CTL were not effective in reducing JHMV replication within the CNS. The distribution of CD4+ and CD8+ T cells within the CNS during JHMV infection showed that the CD4+ T cells remained in perivascular and subara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…These findings raise the possibility that differences affecting the CD4 ϩ T cell compartment may lead to the distinct regulation of JHMV-specific T cells in infected MT vs J H D mice (26). An indirect effect on CD4 ϩ T cells, to explain discrepant T cell function in the absence of B cells, is supported by the fact that CD4 ϩ T cells enhance JHMV-specific CD8 ϩ T cell expansion and function (23,26).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These findings raise the possibility that differences affecting the CD4 ϩ T cell compartment may lead to the distinct regulation of JHMV-specific T cells in infected MT vs J H D mice (26). An indirect effect on CD4 ϩ T cells, to explain discrepant T cell function in the absence of B cells, is supported by the fact that CD4 ϩ T cells enhance JHMV-specific CD8 ϩ T cell expansion and function (23,26).…”
Section: Discussionmentioning
confidence: 91%
“…The ability of B cells from naive donors to lyse virus-infected cells through an interaction between the viral S protein and the viral receptor is unique to mouse hepatitis virus (29,46). Although B cells express the mouse hepatitis virus receptor in vivo (29,47), they appear resistant to infection in vivo based on the inability to detect viral Ag in lymphocytes (22)(23)(24). As cytolysis is inhibited by anti-S protein Ab (29,47,48), a B cell cytolytic mechanism in vivo can only be active before anti-S protein Ab secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the requirement for CD4 help in priming CD8 ϩ T cell responses. However, certain pathogens, including acute lymphocytic choriomeningitis virus and Listeria monocytogenes, are CD4-independent (51)(52)(53)(54). Using L. monocytogenes as a model, Shedlock et al (51) has shown that CD8 ϩ T cell responses are likely to require CD4 help when the pathogen is not immunogenic enough to directly activate APCs.…”
Section: Discussionmentioning
confidence: 99%
“…sarcoma, but in this system, endogenous APC may have been bypassed because the vaccine consisted of cultured, Ag-pulsed DC (22). However, antiviral CTL responses in the CNS are often strictly CD4 dependent, and CTL function and/or viability have been reported to be lost in the absence of CD4 T cells (58,59). Maintenance of CTL function in the brain is clearly dependent upon many factors that differ according to the model used.…”
Section: Cd62lmentioning
confidence: 99%